KEMAMPUAN ISOLAT TUNGGAL DAN KONSORSIUM AKTINOMISETES LOKAL RIAU DALAM MENDEGRADASI HIDROKARBON MINYAK BUMI - Novalita Dwi Fanny; Tetty Marta Linda; Atria Martina (BIO-SITE |Biologi dan Sains Terapan, 2018)
Pollution of crude oil on environmental can have an effect of nutrient uptake on plants and balance of ecosystems. Biodegradation. is one way to reduce petroleum pollution . The purpose of this research are determine the potential growth of actinomycetes local Riau (L11 and L121) in crude oil hydrocarbons at concentrations of 0%, 2%, 5% and to know their ability to degrade crude oil hydrocarbons at concentrations of 5%. This research observed the growth of each actinomycetes local Riau and the percentage of crude oil degradation by a single isolate and a consortium with gravimetric method. The results showed that the growth of L11 and L121 total population was not significantly different at addition crude oil of 2% and 5% but significantly different wth 0% (without crude oil). Test degradation of crude oil using single isolate gave significantly different results for the consortium isolates. Percentage of degradation crude oil by L11 was 23.5%, L121 was 19.2% and consortium isolate (L11 + L121) was 31.9% with an incubation time of 10 days in a minimum medium salts. This actinomycetes local Riau can be developed as biodegradation agents for crude oil on soil and water.